2019
DOI: 10.1152/ajplung.00104.2018
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of retinoic acid signaling induces aberrant pericyte coverage and differentiation resulting in vascular defects in congenital diaphragmatic hernia

Abstract: The mortality and morbidity of patients with congenital diaphragmatic hernia (CDH) is primarily caused by treatment-resistant, persistent pulmonary hypertension. Structural vascular changes, exemplified by extensive muscularization, are already present early in gestation, but the origin of these abnormalities is unknown. Understanding the origin of the vascular defects is important to improve treatment modalities. Here, we show that the distribution of pericytes is different and may thereby potentially initiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 35 publications
2
23
0
Order By: Relevance
“…CDH is a perplexing congenital lung anomaly whose exact cause remains unknown. 39 Although somatic mutations in GATA4 and FOG2, among others, have been implicated in less than 10% of CDH patients, 15,16,40 the etiology of CDH is heterogeneous and likely polygenic in the majority of cases. 12 Regardless, the downstream result of the near-term CDH fetal lung is progressive hypoplasia involving both proximal and distal airways as well as abnormalities within the adjacent mesenchyme and airway smooth muscle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CDH is a perplexing congenital lung anomaly whose exact cause remains unknown. 39 Although somatic mutations in GATA4 and FOG2, among others, have been implicated in less than 10% of CDH patients, 15,16,40 the etiology of CDH is heterogeneous and likely polygenic in the majority of cases. 12 Regardless, the downstream result of the near-term CDH fetal lung is progressive hypoplasia involving both proximal and distal airways as well as abnormalities within the adjacent mesenchyme and airway smooth muscle.…”
Section: Discussionmentioning
confidence: 99%
“…CDH is a perplexing congenital lung anomaly whose exact cause remains unknown 39 . Although somatic mutations in GATA4 and FOG2 , among others, have been implicated in less than 10% of CDH patients, 15,16,40 the etiology of CDH is heterogeneous and likely polygenic in the majority of cases 12 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review of randomized trials supported vitamin A supplementation for the prevention of BPD (173), and a randomized controlled trial to evaluate the use of enteral vitamin A for reducing the severity of BPD has been proposed (479). Recent evidence has also been provided for a role for vitamin A signaling in vascular development, where inhibition of retinoic acid signaling induced aberrant pericyte coverage and differentiation, which was thought to contribute to the disease mechanisms operative in CDH (275). In contrast to vitamins A and D, studies on vitamin C have been restricted to calls for further studies on the utility of vitamin C supplementation during pregnancy to improve fetal lung development in smoking mothers (366,381).…”
Section: Vitaminsmentioning
confidence: 99%
“…Simultaneously, RA acts autocrinally controlling endothelial cell proliferation and tube formation [108]. More recently, it has been demonstrated that RA signaling is involved in pericyte migration, angiogenesis, and collagen IV expression [141].…”
Section: Vascular Developmentmentioning
confidence: 99%